Amelioration of inflammatory myopathies by glucagon‐like peptide‐1 receptor agonist via suppressing muscle fibre necroptosis. Issue 4 (30th June 2022) - Kamiya, Mari; Mizoguchi, Fumitaka; Yasuda, Shinsuke
Abstract: Background: As glucocorticoids induce muscle atrophy during the treatment course of polymyositis (PM), novel therapeutic strategy is awaited that suppresses muscle inflammation but retains muscle strength. We recently found that injured muscle fibres in PM undergo FASLG‐mediated necroptosis, a form of regulated cell death accompanied by release of pro‐inflammatory mediators, contributes to accelerate muscle inflammation and muscle weakness. Glucagon‐like peptide‐1 receptor (GLP‐1R) agonists have pleiotropic actions including anti‐inflammatory effects, prevention of muscle atrophy, and inhibition of cell death, in addition to anti‐diabetic effect. We aimed in this study to examine the role of GLP‐1R in PM and the effect of a GLP‐1R agonist on in vivo and in vitro models of PM. Methods: Muscle specimens of PM patients and a murine model of PM, C protein‐induced myositis (CIM), were examined for the expression of GLP‐1R. The effect of PF1801, a GLP‐1R agonist, on CIM was evaluated in monotherapy or in combination with prednisolone (PSL). As an in vitro model of PM, C2C12‐derived myotubes were treated with FASLG to induce necroptosis. The effect of PF1801 on this model was analysed. Results: GLP‐1R was expressed on the inflamed muscle fibres of PM and CIM. The treatment of CIM with PF1801 in monotherapy (PF) or in combination with PSL (PF + PSL) suppressed CIM‐induced muscle weakness (grip strength, mean ± SD (g); PF 227 ± 6.0 ( P  < 0.01), PF + PSL 224 ± 8.5 ( P  < 0.01), Vehicle 162 ± 6.0) and decrease in cross‐sectional area of muscle fibres (mean ± SD (μm 2 ); PF 1896 ± 144 ( P  < 0.05), PF + PSL 2018 ± 445 ( P  < 0.01), Vehicle 1349 ± 199) as well as the severity of histological inflammation scores (median, interquartile range; PF 0.0, 0.0–0.5 ( P  < 0.05), PF + PSL 0.0, 0.0–0.0 ( P  < 0.01), Vehicle 1.9, 1.3–3.3). PF1801 decreased the levels of inflammatory mediators such as TNFα, IL‐6, and HMGB1 in the serum of CIM. PF1801 inhibited necroptosis of the myotubes in an AMP‐activated protein kinase (AMPK)‐dependent manner. PF1801 activated AMPK and decreased the expression of PGAM5, a mitochondrial protein, which was crucial for necroptosis of the myotubes. PF1801 promoted the degradation of PGAM5 through ubiquitin‐proteasome activity. Furthermore, PF1801 suppressed FASLG‐induced reactive oxygen species (ROS) accumulation in myotubes, also crucial for the execution of necroptosis, thorough up‐regulating the antioxidant molecules including Nfe2l2, Hmox1, Gclm, and Nqo1 . Conclusions: GLP‐1R agonist could be a novel therapy for PM that recovers muscle weakness and suppresses muscle inflammation through inhi biting muscle fibre necroptosis.